Malfunctioning peritoneal dialysis catheter repaired by laparoscopic surgery - Ilhan, YS; Cifter, C; Cetinkaya, Z; Dogru, O; Akkus, MA; Bulbuller, A (Medimond S R L, 1998)
Laparoscopic operations were performed to correct malfunctional Tenckhoff catheters of ten patients treated by continious ambulatory peritoneal dialysis (CAPD) for chronic renal failure. In this method 3 ports (one for the camera and two for the grassper and dissector) are sufficient to perform the operation. Malfunction was found to be due to catheter entrapment or endoluminal tamponing by the omentum. We performed omentectomy in 3 patients and catheter repositioning in 7 patients. Ali the catheters were controled by flashing with Ringer lactate solution. At the end of the follow up period of 8 weeks ail of the catheters were functional. In conclusion; we can say that the laparoscopic reduction of malfunctioning peritoneal dialysis catheters can be thought as an effective method.
6th World Congress of Endoscopic Surgery -- JUN 03-06, 1998 -- ROME, ITALY